Talking about spirituality in health care practice : a resource for the multi-professional health care team - White, Gillian, 1957- (Jessica Kingsley Publishers, 2006)
Health care professionals who endeavour to work holistically face a number of questions about spirituality. What is meant by 'spirituality' as opposed to 'religion'? What is its specific relevance to health care practice?. This accessible book provides answers to these questions and offers a model for personal and professional development. Gillian White sets out a framework within which health care professionals can discuss spirituality and equip themselves to respond appropriately to the spiritual concerns of their patient in daily practice. She draws on her experience of sharing and discussi.